Assessment of Coping Strategies of Elderly regarding Retirement - Jaafar S Al-Showaily; Marwa Jabbar Saiwan; Ghaniyah Mohammed Ghali (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Population ageing represents one of the most significant demographic shifts of the 21st century, with older adults facing profound social and psychological transitions following retirement. Specific Background: Retirement marks a critical life phase characterized by shifts in income, identity, and social roles, requiring adaptive coping mechanisms to maintain well-being. Knowledge Gap: While global research has explored retirement adjustment, limited studies in Iraq have examined how elderly populations cope with this transition and their awareness of retirement-related issues. Aims: This study aimed to assess coping strategies among retired older adults and evaluate their knowledge regarding retirement. Results: Using a descriptive design and a purposive sample of 100 retired individuals, the findings revealed that 70% lacked awareness of the legal retirement age, and 55.5% actively employed coping strategies, predominantly passive mechanisms such as avoidance or dependence reduction. Novelty: The study offers one of the first localized insights into Iraqi retirees’ psychological and behavioral adjustments to retirement, emphasizing the socio-cultural influences on coping behavior. Implications: The findings underscore the need for public education, psychosocial support programs, and policy initiatives that promote proactive coping and retirement preparedness among older adults to enhance post-retirement quality of life.Highlight : About 70% of seniors are unaware of the legal retirement age. Around 55.5% of elderly retirees use coping strategies for adjustment. Raising awareness through education and media can improve retirement coping. Keywords : Ageing Population, Older Adults, Retirement, Life Transition, Demographic Changes